Small bowel arteriovenous malformation as a cause of dark gastrointestinal bleeding: Two instructional cases: Malformación arteriovenosa en intestino delgado como causa de sangrado gastrointestinal oscuro: Dos casos aleccionadores - Palomino Portilla, Eugenio Américo (2023)
ABSTRACT Introduction: Digestive bleeding can put patients’ lives at risk, even more so when the origin is not located in routine upper and lower endoscopy. The small intestine is the largest portion of the digestive tract and being a source of bleeding means a diagnostic and therapeutic medical challenge. Clinical case: We presented cases of two female patients, 53 and 60 years old, who develop digestive bleeding, locating its origin in the small bowel and undergoing surgical removal of the affected intestinal segment. The anatomopathological study finds malformed arteries and veins that communicate without an intermediate capillary bed. The diagnosis was arteriovenous malformation, a rare entity in the small bowel. Both cases are reviewed with emphasis on the histopathological criteria and their clinical correlation. Keywords: Arteriovenous malformation, small bowel, obscure digestive bleeding.